Hazard analysis critical control point and self-regulation - Eglezos, S.; Dykes, Gary (2014)
© 2014 Elsevier Ltd. All rights reserved. As the responsibility of food manufacturers for the safety of their products increases, self-regulatory systems that effectively control food safety risks will undoubtedly proliferate. Food processors and food inspection authorities must cooperate in systematically implementing these systems if they are to be effective. The systems described here, namely good manufacturing practices, hazard analysis critical control point, and failure mode and effect analysis, are only a few of the large number of management tools that can be used for assuring food safety.